2018
DOI: 10.1097/md.0000000000012749
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nursing intervention on preoperative cataract

Abstract: This retrospective study investigated the effect of nursing intervention (NIV) in Chinese patients under preoperative cataract (PC). A total of 70 eligible patients with PC were included. Thirty-five patients in an intervention group received regular clinical treatment and NIV before the surgery, while the other 35 patients received regular clinical treatment only. The NIV was applied 4 sessions, 1 week before the surgery. The primary outcome of satisfaction was measured by 11-points visual analog scale. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
8
Order By: Relevance
“…This brings very good results in terms of reducing anxiety and improving patient cooperation during surgery. 40 , 41 Many of the operated patients seemed happy with an explanation rather than sedation. It must be remembered that sedation, although it reduces anxiety, reduces the patient’s ability to cooperate during the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This brings very good results in terms of reducing anxiety and improving patient cooperation during surgery. 40 , 41 Many of the operated patients seemed happy with an explanation rather than sedation. It must be remembered that sedation, although it reduces anxiety, reduces the patient’s ability to cooperate during the operation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that informative, educational, and planned nursing care has a very beneficial effect on reducing the level of anxiety in patients undergoing cataract surgery. 54 Gong et al 40 showed that nursing intervention, in the form of several meetings in the week immediately preceding admission to the hospital, significantly reduced preoperative anxiety, improved cooperation between the patient and medical staff during surgery, and increased satisfaction with postoperative outcomes. These meetings included psychological support for the patient, helped in preparing for the procedure, and provided the necessary information on the structure of the eye, cataracts and its treatment, as well as on pain management and postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…As previous research has shown, nursing interventions (eg, instructing and explaining the procedure to patients) can be helpful for reducing anxiety and increasing patient satisfaction. 15 Accordingly, including nurses as an integral part of the preoperative process should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that a few conversations with a nurse during the week preceding hospital admission might improve both patients’ cooperation with medical personnel during the surgery and their satisfaction with the postoperative outcomes. 37 The authors of that study emphasized that such conversations, during which, the nurse discusses eye anatomy, pathomechanism of cataract, the protocol of cataract surgery, preparation for the procedure, postoperative pain management and eye rehabilitation, might soothe negative emotions of patients during subsequent stages of phacoemulsification. 37 The role of nurses in the education of patients with cataract was also highlighted by other authors.…”
Section: Discussionmentioning
confidence: 99%
“… 37 The authors of that study emphasized that such conversations, during which, the nurse discusses eye anatomy, pathomechanism of cataract, the protocol of cataract surgery, preparation for the procedure, postoperative pain management and eye rehabilitation, might soothe negative emotions of patients during subsequent stages of phacoemulsification. 37 The role of nurses in the education of patients with cataract was also highlighted by other authors. 38–40 …”
Section: Discussionmentioning
confidence: 99%